2014
DOI: 10.1007/s00404-014-3444-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes of induced labor in women with previous cesarean section: a systematic review and meta-analysis

Abstract: Induction of labor increases the risk of uterine rupture/dehiscence and of repeat cesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 19 publications
5
29
1
6
Order By: Relevance
“…Maternal morbidity, uterine rupture, blood transfusion and hysterectomy were more common after failed TOL (17%, 4.4%, 3% and 0.5%, respectively) than after successful VBAC (3.1%, 0.2%, 1.1% and 0.1%, respectively) or ERCD (4.3%, 0.4%, 1% and 0.3%, respectively). A more recent meta-analysis indicated that induction of labour increases the risk of uterine rupture in women with a prior Cesarean delivery [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal morbidity, uterine rupture, blood transfusion and hysterectomy were more common after failed TOL (17%, 4.4%, 3% and 0.5%, respectively) than after successful VBAC (3.1%, 0.2%, 1.1% and 0.1%, respectively) or ERCD (4.3%, 0.4%, 1% and 0.3%, respectively). A more recent meta-analysis indicated that induction of labour increases the risk of uterine rupture in women with a prior Cesarean delivery [13].…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent meta-analysis of articles published from 1989 to 1999 reported a higher rate of uterine rupture and perinatal death following TOL than with ERCD [12]. More recently, an apparent increase in the frequency of uterine rupture and concern about maternal and perinatal morbidity has called into question the safety and appropriateness of TOL and VBAC [6], and a 2015 meta-analysis indicated that induction of labour in patients with a prior Cesarean delivery increases the risk of uterine rupture and repeat Cesarean delivery [13].…”
mentioning
confidence: 99%
“…O uso da sonda de Foley na indução de parto vem sendo estudado, pois se torna uma boa opção quando a paciente apresenta alguma contraindicação ao uso de métodos farmacológicos, como uma cicatriz uterina prévia [10][11][12]16,17 . A ideia desta pesquisa partiu da necessidade de descrever na nossa população a efetividade e segurança da utilização da sonda na indução do parto e comparar os desfechos com a literatura.…”
Section: Discussionunclassified
“…Essa necessidade resolutiva dos plantonistas corrobora um estudo que sugere que a presença da sonda de Foley é um fator de risco isolado para uma nova cesariana 20 . Outras publicações observaram que pacientes com cesárea anterior que desencadearam o trabalho de parto espontâneo tiveram menores taxas de cesarianas, quando comparadas com mulheres que iniciaram a indução com sonda de Foley 10,20,22 . Destacamos que todas as nossas gestantes tiveram o trabalho de parto induzido com sonda de Foley, diferente dos estudos mencionados, que compararam a indução com o parto espontâneo.…”
Section: Intervalo Da Colocação Da Sonda E O Parto (Variação) (N=9) 4unclassified
See 1 more Smart Citation